High-risk sexual behaviours among gay and bisexual men: Comparing event-level casual sex encounters among seroconverters and non-seroconverters - Down, I.; Ellard, J.; Triffitt, K.; Zablotska, I.; Hurley, M.; Brown, Graham; Bradley, J.; Prestage, G. (BMJ Publishing Group, 2017)
Background: With increasing use of non-condom-based HIV risk reduction strategies by gay and bisexual men (GBM), we compared occasions of condomless anal intercourse with casual partners (CLAIC) that resulted in HIV transmission and similar occasions when HIV transmission did not occur. Methods: We compared two demographically similar samples of Australian GBM. The HIV Seroconversion Study (SCS) was an online cross-sectional survey of GBM recently diagnosed with HIV. The Pleasure and Sexual Health (PASH) study was an online cross sectional survey of GBM generally. Using logistic regression, we compared accounts of CLAIC reported by men in SCS as being the event which led to them acquiring HIV, with recent CLAIC reported by HIV-negative men in PASH. Results: In SCS, 85.1% of men reported receptive CLAIC, including 51.8% with ejaculation; 32.1% reported having previously met this partner and 28.6% believed this partner to be HIV-negative. Among HIV-negative men in PASH reporting recent CLAIC, 65.5% reported receptive CLAIC, including 29.9% with ejaculation; 59.3% reported having previously met this partner and 70.1% believed this partner to be HIV-negative. Conclusions: While both groups of men engaged in CLAIC, how they engaged in CLAIC differed, and the context in which they did so was different. A generic measure of CLAIC conceals the critical elements of HIV risk, particularly the role of receptive CLAIC, among GBM that distinguish those who seroconverted and those who did not. Detailed information about the context and nature of the practise of CLAIC is required for a more complete understanding of HIV risk among GBM.